اجتہاد کا معنی و مفہوم اور اقسامِ : ایک تحقیقی مطالعہ (Al-Qamar, 2022)
Ijtihād, (Arabic: “effort”) in Islamic law, the independent or original interpretation of problems not precisely covered by the Qurʾān, Hadith (traditions concerning the Prophet Muhammad’s life and utterances), and Ijmāʿ (scholarly consensus). In the early Muslim community, every adequately qualified jurist had the right to exercise such original thinking, mainly in the form of raʾy (personal judgment) and qiyās (analogical reasoning), and those who did so were termed mujtahids. But with the crystallization of legal schools (madhhabs) under the ʿAbbāsids (reigned 750–1258), jurists of the majority Sunni branch of Islam came to be associated with one or another of the schools of law and formulated their legal thought within the framework of their school’s interpretive principles and against the backdrop of its doctrinal precedent. Over time, individuals’ qualifications to exercise ijtihād were organized into levels, ranging from the absolute mujtahid, who was bound by no precedent and free to develop his own interpretive principles, to the absolute muqallid (“follower,” “layperson”), who was required to follow authoritative jurists unquestioningly.
Keywords: Ijtihad; Qurʾān; Prophet Muhammad; original thinking; legal thought; organized; unquestioningly